Konsep dan Operasionalisasi Model SAMR dalam Pembelajaran PAI - Moch. Khotibul Ummam; Lailiyatul Maulidah; Mochammad Syihabbudin (Universitas Islam Lamongan, 2021)
The development of education from time to time will always be followed by technological developments. Character education through Islamic Education learning is needed by students in an increasingly sophisticated era with increasingly modern technology. With the development of technology in the world of education, technology can help education by using modern learning models. The findings in this study are that technology can be integrated using the SAMR (Substitution, Augmentation, Modification, and Redefinition) model so that it can improve the quality of education better. The author considers that technology integration in learning with the SAMR model is very necessary, so that educators can more easily achieve goals in learning. In this journal, we will review how technology integration in Islamic Education learning using the SAMR model.